Nanosilicon: An approach for abiotic stress mitigation and sustainable agriculture - Verma, Krishan K.; Zeng, Yuan; Song, Xiu-Peng; Singh, Munna; Wu, Kai-Chao; Rajput, Vishnu D.; Li, Yang-Rui (Frontiers in Plant Science, 2022)
Abiotic stresses causing extensive yield loss in various crops globally. Over the past few decades, the application of silicon nanoparticles (nSi) has emerged as one of the abiotic stress mitigators. The initial responses of plants are shown by the biogenesis of reactive oxygen species (ROS) to sustain cellular/organellar integrity to ensure in vivo operation of metabolic functions by regulating physiological and biochemical pathways during stress conditions. Plants have evolved various antioxidative systems to balance/ maintain the process of homeostasis via enzymatic and non-enzymatic activities to repair the losses. In the adverse environment, supplementation of Si mitigates the stress condition and improved the growth and development of plants. Its ameliorative effects were correlated with the enhanced antioxidant enzymes activities to maintain the equilibrium between the ROS generation and reduction. However, there are limited studies covered the role of nSi in the abiotic stress condition. This review addresses the accumulation and/ or uptake of nSi in several crops and its mode of action linked with improved plants’ growth and tolerance capabilities to confer sustainable agriculture.